LAPORAN KASUS: DERMATITIS KONTAK IRITAN - Amara Aurelia; Hapsari Triandriyani; Hadi Firmansyah (Cahaya Ilmu Bangsa Institute, 2024)
ABSTRACT Background: Contact dermatitis is an inflammatory skin condition caused by exposure to chemicals or irritants that damage the skin's protective barrier, divided into irritant contact dermatitis (ICD), which does not involve an immune response, and allergic contact dermatitis (ACD), which is mediated by an immune reaction, with ICD often being difficult to detect clinically and requiring avoidance of irritants as the primary treatment. Objective: This case report aims to provide a diagnostic overview and management of a patient with Irritant Contact Dermatitis. Method: A case is reported of a 33-year-old female patient presenting with peeling skin between her fingers accompanied by pain and itching. Examination, including anamnesis and dermatological status, was conducted to establish the diagnosis. Results: The diagnosis of Irritant Contact Dermatitis relies on patient anamnesis, physical examination, and supporting tests to differentiate it from Allergic Contact Dermatitis. Conclusion: The diagnosis of irritant contact dermatitis (ICD) in the patient was established through anamnesis, physical examination, and patch testing to rule out allergic contact dermatitis, with management including irritant avoidance, use of personal protective equipment, topical corticosteroids, systemic medications if necessary, and long-term education to prevent recurrence. ABSTRAK Latar Belakang: Dermatitis kontak adalah penyakit kulit eksim inflamasi yang disebabkan oleh paparan bahan kimia atau iritan yang merusak lapisan pelindung kulit, terbagi menjadi dermatitis kontak iritan (DKI) yang tidak melibatkan respons imun dan dermatitis kontak alergi (DKA) yang dimediasi oleh reaksi imun, dengan DKI sering kali sulit terdeteksi secara klinis dan memerlukan penghindaran bahan iritan sebagai terapi utama. Tujuan: Laporan kasus ini bertujuan untuk memberikan gambaran diagnostik dan penatalaksanaan pada pasien Dermatitis Kontak Iritan. Metode: Dilaporkan kasus seorang pasien Perempuan berusia 33 tahun dengan keluhan kulit pada sela jari yang terkelupas disertai perih dan gatal. Pemeriksaan seperti anamnesis serta status dermatologikus dilakukan untuk menegakkan diagnosis. Hasil: Diagnosis Dermatitis Kontak Iritan tidak lepas dari anamnesis dan pemeriksaan fisik pasien, serta pemeriksaan penunjang untuk membedakan dengan diagnosa Dermatitis Kontak Alergi. Kesimpulan: Diagnosis dermatitis kontak iritan (DKI) pada pasien ditegakkan melalui anamnesis, pemeriksaan fisik, dan uji tempel untuk menyingkirkan dermatitis kontak alergi, dengan penatalaksanaan meliputi penghindaran iritan, penggunaan alat pelindung diri, kortikosteroid topikal, serta obat sistemik jika diperlukan, dan edukasi jangka panjang untuk mencegah kekambuhan.